The effect of vernix caseosa in preventing nipple problems among early postpartum women: A randomized-controlled single-blind clinical trial** - POTUR, DİLEK (ELSEVIER SCI LTD, 2021)
Background and purpose: Vernix caseosa, a natural substance similar to mother's milk with protective effects on the skin, might be effective in preventing nipple problems. The purpose of this study was to examine the potential efficacy of vernix caseosa compared to the conventional use of mother's milk in the prevention of postpartum nipple problems. Materials and methods: This randomized, controlled, single-blind experimental study involved 64 primipara mothers who underwent cesarean section and were randomly and equally divided between the vernix caseosa group and the mother's milk group. All mothers received nipple care four times daily during the first postpartum week. Data were collected using personal information and nipple monitoring forms. Results: The incidence of nipple pain, rashes, and an abnormal appearance was similar in both groups on the first day postpartum (p = 0.132, p = 0.516, and p = 0.132, respectively), and none of the mothers had nipple cracks. On the seventh day, mothers in the vernix caseosa group had significantly less pain (p = 0.042), significantly reduced rash (p = 0.048), significantly higher satisfaction (p = 0.023), and no nipple cracks. Conclusion: Nipple care with vernix caseosa is more effective than with mother's milk in preventing postpartum nipple pain, rashes, and cracks.
Keywords: Breastfeeding; Nipples; Postpartum period; Vernix caseosa; BREAST-FEEDING PROBLEMS; DAMAGED NIPPLES; MOTHERS; LANOLIN; MILK; PAIN